Effect of emotion on hawk-dove game for two players with different strength - Yajie Gao; Hui Long; Zhineng Wang; Renzhen Chen (Scientific Reports)
Abstract Players’ emotion greatly affect their behaviors in conflicts but is usually ignored in current Hawk-Dove games. To describe the game more realistically, a strength gap is defined as a difference between two players’ strength coefficients and is employed to propose an asymmetric hawk-dove game. A rank-dependent expected utility theory is also employed to describe the effects of players’ emotion on their decisions. A new Hawk-Dove game model incorporating the strength gap and emotion is then proposed. Effects of emotion on this new game are theoretically analyzed and numerically verified using Matlab software. Results show that emotion has no effect on the hawk-dove game at a large strength gap or under a condition of non-negative net income. But it greatly plays a role under a condition of a small strength gap and negative net income. There is a rule in the emotional world that the same sexes attract and the opposite sexes repel in a vicious competitive environment where individuals earn little but take significant risks. A rational attitude prevents an opponent’s decisions from being influenced by their own emotion. And a happier attitude promotes the opponent to choose more peaceful behaviors in conflicts.